2017
DOI: 10.1016/j.bbr.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular aspects of age-related cognitive decline and Alzheimer’s disease

Abstract: As the population of people aged 60 or older continues to rise, it has become increasingly important to understand the molecular basis underlying age-related cognitive decline. In fact, a better understanding of aging biology will help us identify ways to maintain high levels of cognitive functioning throughout the aging process. Many cellular and molecular aspects of brain aging are shared with other organ systems; however, certain age-related changes are unique to the nervous system due to its structural, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 273 publications
2
18
0
1
Order By: Relevance
“…To dissect how changes in cytosol-to-ER flux of acetyl-CoA might affect the secretory pathway, we used mass spectrometry-based strategies 14 to examine the proteome and acetyl-proteome (stoichiometry of lysine acetylation) of AT-1 sTg and AT-1 S113R/+ mice. The effect of these genetic manipulations to the cytosol-to-ER flux of acetyl-CoA is reported elsewhere 4 , 6 , 14 , 15 . The analysis identified dynamic changes to protein abundance and acetylation across several essential and functional components of the secretory pathway (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…To dissect how changes in cytosol-to-ER flux of acetyl-CoA might affect the secretory pathway, we used mass spectrometry-based strategies 14 to examine the proteome and acetyl-proteome (stoichiometry of lysine acetylation) of AT-1 sTg and AT-1 S113R/+ mice. The effect of these genetic manipulations to the cytosol-to-ER flux of acetyl-CoA is reported elsewhere 4 , 6 , 14 , 15 . The analysis identified dynamic changes to protein abundance and acetylation across several essential and functional components of the secretory pathway (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…More recently, a study by Jamshed et al in 2019 showed that time-restricted feeding early in the day tended to increase brain-derived neurotrophic factor as well as have a potential anti-ageing effect by increasing gene expression of longevity genes SIRT1 and MTOR [62]. In the human lifespan, age-related cognitive decline is a natural part of the ageing process, potentially due to the decline in AHN [9,63]. It has been suggested that young new-born neurons within the dentate gyrus may be responsible for mediating pattern separation and as they age mediate the ability to trigger "pattern completion-mediated recall", i.e., recognition memory [64].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, biomarkers per se should offer a window to the pathological processes coupled to the development and progression of AD [ 4 ] and clearly distinguish between these processes and those related to normal aging. Aging alone is one of the major risk factors for AD [ 5 ], but little is known about the molecular processes that distinguish healthy aging from pathological aging [ 6 ]. In addition to accumulation of amyloid-β (Aβ) peptides and hyperphosphorylated tau, other age-related alterations such as processes linked to inflammation are believed to play an important role in AD pathogenesis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%